Human Design Parameters for Safety of Products and Systems - Iino Kenji; Nakao Masayuki (MATEC Web of Conferences, 2018)
Designers spend much efforts in defining their products and systems, planning how they work during normal operation. Design assisting tools like Design Matrices in Axiomatic Design (AD) or Design Record Graphs (DRG) are available to the designer in search for ways to improve their work. Majority of accidents, however, take place during irregular operations like maintenance when interlocks are often bypassed and automatic processing are switched to manual. System safety is then in the hands of human operators. A number of past AD studies have addressed safety in products and systems, however, design parameters (DPs) have been physical parts or structures. This paper shows assignment of human actions, like, “reading the quantity display,” “making judgement,” or “pressing a control button,” as DPs in axiomatic design. Such human DPs play important roles during maintenance, nevertheless, designers often leave out safety evaluation of their designs in this maintenance mode. When a human DP fails to meet its functional requirement (FR), the product often faces failure and the system often heads into an accident. Identifying human DPs in products or systems thus alerts maintenance phase workers about actions that are critical for safety. Most accidents take place with excessive dependence on human DP of memory.